The Influence of the Artistic Image on the Poetics of the Work (In the example of the epics "Mantiq utTair" and "Lison ut-Tair") - Karimova Yulduz Bakhtiyorovna (Genius Publishing Group, 2022)
In this article, the impact of the artistic image on the poetics of the work was studied based on the stories of Fariduddin Attar's "Mantiq ut-Tair" and Alisher Navoi's "Lison ut-Tair" epics, which are close to each other in terms of content. The fact that the artistic image is a component of the poetics of the work, it is manifested in the description of the characters, in the analysis of their inner world and in the drawing of their external appearance, in the narration of episodes that help to reveal a certain side of reality.
Keywords: Poetics; Artistic Speech; Artistic Thinking; Style